Designing Literature-based Instruction Materials for Sixth Grade Students of Elementary School - Ni Putu Artila Dewi (Jurnal Ilmiah Sekolah Dasar, 2020)
This research aims to develop literature-based instruction materials for sixth grade students of elementary school through story. The method of this research is Design and Development. In developing literature-based instruction materials, this research uses DnD model by Richey and Klien. Some several processes were carried out, such as: 1) Analysing thematic syllabus of sixth grade students to get the topic for materials. 2) Designing to develop blueprint the literature-based instruction material and designing English short story and mini lesson plan by combining the result of analysis and mapping out from the thematic syllabus. 3) Developing English short story and mini lesson plan to become prnted materials book for sixth grade students of elementary school. 4) Evaluating the results of English short story and mini lesson plan. The result of this research revealed ten stories needed, namely: The Snail Race, Master Brawa, The Sun, Bobby and friends, The Good Lion, The Peace Jungle, Three Neighbors, The Winning Team, Prince Panji, and The Fisher. The results of evaluation from experts concluded that the quality of the books developed was very good material